Extraction of protein and carbohydrates from soybean meal using acidic and alkaline solutions produced by electro‐activation. Issue 2 (21st January 2020) - Gerliani, Natela; Hammami, Riadh; Aïder, Mohammed
Abstract: This main objective of this work was to study the extraction of proteins and soluble carbohydrates and minerals from soybean meal by using acidic (anolyte) and alkaline (catholyte) extracting solutions produced by electro‐activation technology. The extracting solutions (anolyte and catholyte) were produced by electro‐activation at current intensities of 150, 300, and 450 mA during 10, 30, and 50 min. Both extraction methods were effective in extracting soluble dry matter. The catholyte was the most efficient in extracting proteins with a maximal yield of 45.55 ± 2.77%. Moreover, protein content increased with treatment time in catholyte extracts but decreased in anolyte‐extracted samples. SDS‐PAGE confirmed catholyte effectiveness in extracting more proteins with better quality than the anolyte. Similar results were observed for amino acid profiles, with samples extracted by the catholyte being the richest in both essential and nonessential amino acids. While the anolyte extracted the highest amounts of Mg 2+ (78%), Ca 2+ (37%), and P 3− (37%) from the soybean meal, catholyte was more efficient in extracting Zn 2+ (65%), Fe 2+ (62%), and Cu 2+ (42%) ions. The obtained samples by both anolytes and catholytes exhibited good carbohydrate profiles containing some prebiotic monosaccharides. The carbohydrate profile varied with voltage used for the production of electro‐activated solutions and time. Stachyose and raffinose content increased with voltage used for anolytes production while decreasing in catholytes samples. Similarly, the highest stachyose and raffinose contents were observed for catholyte‐treated samples for 10 min, with respective ranges of 206.64–222.49 and 31.17–34.29 mg/g. To a lesser extent, anolyte‐treated samples for a longer time (30–50 min) were more efficient in extracting those sugars. Abstract : The objective of this work is to develop sustainable technology for integral valorization of soybean meal for human nutrition by extracting a protein–carbohydrate complex with high nutritional value.